2016
DOI: 10.5455/ijtrr.000000173
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Based Training Program for Motor Functions in Cerebral Palsied Children with Cortical Visual Impairment

Abstract: Background/Aim: Cortical visual impairment (CVI) is a temporary or permanent visual dysfunction resulting from damage to the visual systems in the brain that deal with processing and integrating visual information. The aim of current study was to investigate the effect of visual-based training program on motor functions in cerebral palsied (CP) children with CVI. Methods: Twenty six spastic CP children with CVI from both sex, ranged in age from 2 to 4 years, participated in this study. They were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that motor developmental delay due to motor and proprioceptive loss was observed in infants with cortical vision loss [ 10 ]. According to our study results, motor development delay may be observed in infants with cortical vision loss, but the sensory integration intervention alone cannot contribute to a significant improvement in motor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that motor developmental delay due to motor and proprioceptive loss was observed in infants with cortical vision loss [ 10 ]. According to our study results, motor development delay may be observed in infants with cortical vision loss, but the sensory integration intervention alone cannot contribute to a significant improvement in motor development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have shown the efficacy of sensory integration therapy on fine motor skills [ 8 ] and walking parameters [ 9 ] in children with CP who did not experience CVI. In a randomized controlled study with 26 children aged 2–4 years with CVI and spastic CP, it was found that sensory integration therapy applied in addition to conventional physiotherapy for 3 days a week for 3 months improved gross and fine motor skills [ 10 ].…”
Section: Introductionmentioning
confidence: 99%